Modality and diachronic construction grammar - Hilpert, Martin; Cappelle, Bert, 1975-; Depraetere, Ilse, 1964- (Constructional approaches to language ;, 2021)
"This volume explores how Diachronic Construction Grammar can shed new light on changes in a central and well-researched domain of grammar, namely modality. Its main goal is to show how constructional analyses can help us address some of the long-standing questions that have informed discussions of modal expressions and their development, and to illustrate the processes that are involved in these developments on the basis of data from languages such as English, Finnish, French, Galician, German, and Japanese. The studies in this volume are organized around three interrelated topics. The first of these concerns the organization of modal constructions in a network. A second focus area of the studies in this volume concerns the developmental pathways that modal constructions follow diachronically. The third topic that ties the contributions of this volume together is the contrast between constructionalization and constructional change"--